Corporate Financial Distress: The Impact of Profitability, Liquidity, Asset Productivity, Activity and Solvency - Karikari Amoa-Gyarteng (Journal of Accounting, Business and Management (JABM), 2021)
This study aims to determine the importance of liquidity, profitability, asset productivity, activity, and solvency in cases of corporate financial distress. One hundred and five firms in the extractive industry in the United States were analyzed. Firms must be publicly traded and have filed form 10-K reports with the securities and exchange commission of the United States to be considered for the study’s population. The measure of corporate financial distress is the Altman Z-score. By using the Altman discriminant function, this study identifies the precipitants of corporate financial distress. This is especially important because widespread corporate financial distress could cause global financial system volatility. The indicators were measured in the last two years before the distressed firms declared bankruptcy. The results indicate that liquidity, profitability, asset productivity and solvency have an impact on the financial health of firms and therefore, on financial distress. The study further determines that activity ratio does not have a statistically significant relationship with financial distress.